2010
DOI: 10.1177/1477153510373315
|View full text |Cite
|
Sign up to set email alerts
|

Impact of current supply on LED colour

Abstract: The quality of light emitted by lighting systems based on high brightness LEDs is studied using colorimetric parameters (chromaticity coordinates, correlated colour temperature and colour rendering index) when operating with different forms of electrical power supply (continuous and pulsed current). Uncertainties, calculated by Monte Carlo simulations applied to relative spectral measurements and colorimetric parameters are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…First, energy efficiency is only the most critical performance issue for incandescent bulbs. Other technologies had their own problems, for example flickering and modulation (fluorescent lighting) (Bruxdrett, Grifft, and Boyce 1973, Wilkins and Clark 1990, Veitch and McColl 1995, Berman et al 1997) and color rendering (LEDs) (Sándor and Schanda 2006, Szabó, Bodrogi, and Schanda 2009, Pousset, Rougié, and Razet 2010, Alvi et al 2011, Smet et al 2012). Second, improved energy efficiency was not what the consumers asked for; the pressure to increase energy efficiency instead came mainly from policy in the form of investments in research of more efficient lighting technologies, new regulations (e.g.…”
Section: Expectation Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, energy efficiency is only the most critical performance issue for incandescent bulbs. Other technologies had their own problems, for example flickering and modulation (fluorescent lighting) (Bruxdrett, Grifft, and Boyce 1973, Wilkins and Clark 1990, Veitch and McColl 1995, Berman et al 1997) and color rendering (LEDs) (Sándor and Schanda 2006, Szabó, Bodrogi, and Schanda 2009, Pousset, Rougié, and Razet 2010, Alvi et al 2011, Smet et al 2012). Second, improved energy efficiency was not what the consumers asked for; the pressure to increase energy efficiency instead came mainly from policy in the form of investments in research of more efficient lighting technologies, new regulations (e.g.…”
Section: Expectation Effectsmentioning
confidence: 99%
“…Pousset et al (2010) Solving technical issues of LED lamps related to colour rendering. What was driving the mechanism of see-saw effects during LED advancement across a number of market niches.…”
Section: Source Namementioning
confidence: 99%
“…Studies have shown that there is a close link between the current through the LED and the characteristic parameters of LED, such as luminous flux [4], the main wavelength [5], color temperature, luminous efficiency [6] and chroma [7], etc. Precision current regulation is the key to studying the LED characteristic parameters, thus the LED drive circuit design has become the focus of research.…”
Section: Introductionmentioning
confidence: 99%
“…Having calculated all the parameters, a relationship between the required output capacitance for a certain peak-to-peak current ripple (ΔI) can be made from (18), as,…”
Section: Bmentioning
confidence: 99%
“…In order to comply with the lifetime requirements of ENERGY STAR ® , this work analyzes the reduction of CX, allowing a certain ripple to appear in terms of the current across the LEDs. This ripple will modulate the amplitude of the light due to the well-known relationship between current and light on an LED [18], hence, causing a perceptible flicker on each phase. It should be noted that, this current modulation of a low frequency ac signal plus a dc signal does not have any impact in terms of the lifetime of the LEDs [19].…”
mentioning
confidence: 99%